A case of Plasmodium Falciparum Malaria with initial presentation of diarrhea leading to multi organ failure (Bangladesh Critical Care Journal, 2019)
Malaria is a major health concern in tropical countries. The disease has various modes of presentation involving different organs in the body. Gastrointestinal manifestation is a common mode of presentation, but diarrhea as the initial symptom is rare. The incubation period of Plasmodium falciparum is 9 to 14 days. Due to differences in the presenting symptoms, prompt diagnosis and treatment is most often delayed. Here, we are reporting a 64 years old Dutch male with history of travel to Ghana 45 days back, followed by Netherlands, Myanmar before coming to Rajshahi, Bangladesh, a non-endemic zone of malaria. He was admitted to a peripheral hospital there with history of diarrhea for 2 days and an episode of loss of consciousness. After admission, he developed fever with chills. On the next day his consciousness level deteriorated. The initial PBF revealed no parasite while a second PBF revealed plasmodium falciparum. The patient was transferred to our hospital with endotracheal tube for further management. He later developed AKI, DIC with septic shock, and atrial fibrillation during his stay in our hospital. He was treated with both parenteral and orally administered antimalarial medications.Bangladesh Crit Care J March 2019; 7(1): 48-50